안와격막앞연조직염을 동반한 동양안충 감염 1예 - 이동현(Dong Hyun Lee), 박성희(Sung Hee Park), 유학선(Hak Sun Yu), 이지은(Ji Eun Lee) (Daihan angwa haghoi jabji, 2018)
목적: 안와격막앞연조직염을 동반한 동양안충 감염 1예를 경험하였기에 보고하고자 한다. 증례요약: 24세 여자 환자가 좌안 결막충혈 및 통증과 함께 하측 결막낭에 기생충이 발견되어 내원하였다. Thelazia callipaeda가 동정되었고, 광학 현미경상 자충으로 질구에 다수의 유충이 확인되었다. 3일 후부터 좌안 상안검주위 홍반성 부종이 시작되었고 하측 결막낭에서 4마리 성충이 관찰되어 겸자로 제거하였다. 3세대 세팔로스포린 항생제 및 비스테로이드성 항염증제를 경구투여 하였고, 상안검주위 부종은 호전되었으나 결막충혈은 여전히 남아 있었다. 이후 4주 간격으로 성충 5마리 및 7마리가 각각 관찰되어 제거하였으며, 마지막 제거 이후 결막충혈도 호전 양상을 보였고 기생충은 더 이상 검출되지 않았다. 결론: 동양안충의 경우 충란 및 유충 여부를 확인하는 것이 필요하고, 유충의 성장을 고려하여 1달 이상의 추적 관찰이 필요하겠다. 또한 동양안충에 의한 안와격막앞연조직염의 발생 가능성도 있으므로 이를 염두에 두어야 할 것이다. Purpose: To report a case of Thelazia callipaeda infection with preseptal cellulitis. Case summary: A 24-year-old female presented with symptoms of conjunctival injection and ocular pain in her left eye and a parasite was found in her conjunctival sac. Using light microscopy, we identified Thelazia callipaeda and many larvae were observed in the vulva of an adult female worm. Three days later, erythematous swelling occurred in the left upper eyelid and four adult worms were found and removed with forceps. Third-generation cephalosporin and nonsteroidal anti-inflammatory drugs were administered orally; the eyelid swelling improved but the conjunctival injection remained. Later five and seven adult worms were removed every 4 weeks and the conjunctival injection improved with no parasites detected after the final extraction. Conclusions: In the case of Thelazia callipaeda infection, it is necessary to identify eggs and larvae and to observe the patient for more than 1 month because of postextraction growth of the larvae. In addition, the possibility of preseptal cellulitis by Thelazia callipaeda should be considered. KCI Citation Count: 0